Kegiatan Pengabdian Masyarakat sebagai Pembicara dalam Webinar Ngobrol Bareng Legislator “Berinternet Secara Sehat” - yanto TIUAJ (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
This community service activity is to provide an explanation regarding various health problems due to smartphone use in digital era. There were three speakers who presented various topics related to healthy internet usage. During presentation, various physical illness related to long-term use of mobile phones were mentioned. Negative aspects from a psychological and social perspective are also discussed. All are caused by a combination of long duration of use, awkward posture and static posture. In the end session, a few suggestions were given to reduce the negative impact of celluler phone usage on physical health. This webinar could be watched via youtube channel